Respuesta :

Answer:

The product is [tex]\frac{3a}{a-2}[/tex].

Step-by-step explanation:

The expression is:

[tex]\frac{2a-7}{a}\times \frac{3a^{2}}{2a^{2}-11a+14}[/tex]

Simplify as follows:

[tex]\frac{2a-7}{a}\times \frac{3a^{2}}{2a^{2}-11a+14}=(2a-7)\times \frac{3a}{2a^{2}-7a-4a+14}[/tex]

                             [tex]=(2a-7)\times \frac{3a}{a(2a-7)-2(2a-7)}\\\\=(2a-7)\times \frac{3a}{(a-2)(2a-7)}\\\\=\frac{3a}{a-2}[/tex]

Thus, the product is [tex]\frac{3a}{a-2}[/tex].

Answer:

the answer to this question is B.

Step-by-step explanation: